2015
DOI: 10.2741/e743
|View full text |Cite
|
Sign up to set email alerts
|

Perception of dyspnea in children with asthma

Abstract: The subjective experience of discomfort in breathing, termed dyspnea (or breathlessness), is a symptom with multifactorial causes of highly complex and largely undefined psycho-physiologic mechanism(s). There are at least three discrete qualities of dyspnea likely corresponding to different types of respiratory stress and separate underlying mechanisms. Perception of dyspnea can be measured by diverse means; however, none of these scales has been standardized in children. In general, the same degree of broncho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…The ability to perceive the onset and severity of symptoms of asthma varies among children and depends on multifactorial causes and very complex and largely undefined psycho-physiological mechanisms [ 12 , 13 ]. The use of peak flow meters (calibrated instruments used to measure lung capacity in monitoring breathing disorders such as asthma) is recommended to help the patient objectify the degree of bronchial obstruction, but previous studies have shown that there is only a weak correlation between objective measures of respiratory distress and the subjective dyspnea sensation described by the patient [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ability to perceive the onset and severity of symptoms of asthma varies among children and depends on multifactorial causes and very complex and largely undefined psycho-physiological mechanisms [ 12 , 13 ]. The use of peak flow meters (calibrated instruments used to measure lung capacity in monitoring breathing disorders such as asthma) is recommended to help the patient objectify the degree of bronchial obstruction, but previous studies have shown that there is only a weak correlation between objective measures of respiratory distress and the subjective dyspnea sensation described by the patient [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%